L‐DOPA‐Coated Manganese Oxide Nanoparticles as Dual MRI Contrast Agents and Drug‐Delivery Vehicles. Issue 3 (30th November 2015) - McDonagh, Birgitte Hjelmeland; Singh, Gurvinder; Hak, Sjoerd; Bandyopadhyay, Sulalit; Augestad, Ingrid Lovise; Peddis, Davide; Sandvig, Ioanna; Sandvig, Axel; Glomm, Wilhelm Robert
Abstract : Manganese oxide nanoparticles (MONPs) are capable of time‐dependent magnetic resonance imaging contrast switching as well as releasing a surface‐bound drug. MONPs give T2/T2 * contrast, but dissolve and release T1‐active Mn 2+ andL ‐3, 4‐dihydroxyphenylalanine. Complementary images are acquired with a single contrast agent, and applications toward Parkinson's disease are suggested.